2015
DOI: 10.12681/mms.1158
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions influencing the larval fish assemblage during summer in the Gulf of Gabes (Tunisia: South central Mediterranean)

Abstract: An oceanographic survey was carried out during the summer of 2009, from June 25 to July 3 in the Gulf of Gabes. The study area was characterised by a wide continental shelf.A plankton sampling scheme was carried out to study the structure of the larval fish assemblages that characterised the surface mixed layer, and to assess the influence of the environmental parameters on their spatial distribution.A total of 36 taxa were identified, three classified to the level of genus, five to the family and 28 to the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The high concentrations of Atlantic bluefin tuna larvae at the offshore stations may be clear evidence that this species tends to avoid the productive coastal waters and prefers the offshore oligotrophic waters, in agreement with earlier ichthyoplankton studies carried out in Tunisia (Koched et al 2012(Koched et al , 2015 and in other areas of the Mediterranean (Oray andKarakulak 2005, Alemany et al 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high concentrations of Atlantic bluefin tuna larvae at the offshore stations may be clear evidence that this species tends to avoid the productive coastal waters and prefers the offshore oligotrophic waters, in agreement with earlier ichthyoplankton studies carried out in Tunisia (Koched et al 2012(Koched et al , 2015 and in other areas of the Mediterranean (Oray andKarakulak 2005, Alemany et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Larvae of the same species, except the Atlantic bonito, have also been collected in other areas of Tunisian waters (Koched et al 2012, 2013, 2015, Zarrad et al 2013) and in the central and eastern part of the Mediterranean (Garcia et al 2005, Tsuji et al 1997, Oray and Karakulak 2005.…”
Section: Discussionmentioning
confidence: 88%
“…The area has been recognized as a phytoplankton blooms ecoregion (Ayata et al, 2018), leading to a small-copepod-dominated-zooplankton density higher than in the TWM (Annabi-Trabelsi et al, 2005;Ben Ltaief et al, 2015;Gueroun et al, 2020). The area is also an essential nursery for several fish species (Koched et al, 2015), contributing to ≈40% of the national fish production. R. pulmo outbreaks might therefore represent, in the first stage, a threat to zooplanktivorous fish larvae recruitment through competition and/or its top-down control of the plankton community, and in the second stage, affect higher trophic levels.…”
Section: R Pulmo (Rhizostomeae Rhizostomatidae)mentioning
confidence: 99%
“…Based on complementary biogeochemical and plankton criteria synthesized from recent regionalization analyses by Ayata et al (2018), the Gulf of Gabès was recently identified as one of the eleven consensus ecoregions of the Mediterranean and classified as a shallow and phytoplankton bloom region. Linked to this planktonic richness, this area is an important nursery for several fish species (Koched et al, 2015;Enajjar et al, 2015) and contributes approximately 40% of the national fish production in Tunisia (DGPA, 2015). However, this singular and economically important region was recently identified as a 'hotspot' of anthropogenic pressures (Reygondeau et al, 2017), strongly threatened by industrialization, particularly discharges from large-scale phosphate production plants, and overfishing, both potentially causing ecosystem disequilibrium and the decline of fish resources (Bejaoui et al, 2019).…”
Section: Study Sitementioning
confidence: 99%